Use of a booster dose of capsular group C meningococcal glycoconjugate vaccine to demonstrate immunologic memory in children primed with one or two vaccine doses in infancy - Pace, D; Khatami, A; Attard-Montalto, S; Voysey, M; Finn, A; Faust, S; Heath, P; Borrow, R; Snape, M; Pollard, A (Elsevier, 2016)
Background Use of a polysaccharide vaccine challenge to demonstrate immunologic memory after priming with capsular group C meningococcal conjugate vaccines (MenCC) risks induction of immunologic hyporesponsiveness. For this reason, MenCC vaccines are now used as probes of immunologic memory, however, no studies have demonstrated their ability to distinguish primed from unprimed children. Methods This study was part of a randomised controlled trial investigating the immunogenicity of a booster dose of the combined Haemophilus influenzae type b and MenC-tetanus toxoid vaccine (Hib-MenC-TT) in infants receiving reduced dose MenCC vaccine priming schedules (one MenC-CRM/MenC-TT or two MenC-CRM vaccine doses) compared with an unprimed group. Antibody kinetics were studied in a subset of 269 children by measuring changes in the MenC serum bactericidal antibody, using rabbit complement, (MenC rSBA) titres and MenC specific IgG memory B-cells before and at 6 and 28 days following the 12 month booster vaccination. Results At 6 days after the 12 month MenCC vaccine, the rise in MenC rSBA titres and MenC specific IgG memory B-cells of the primed groups were significantly higher than the infant MenCC naïve group. Participants primed with one MenC-TT dose had the highest increase in MenC rSBA titres compared with all other groups. The MenC rSBA titres at the 28th compared with the 6th day after boosting was significantly higher in those primed with a single MenC-TT/MenC-CRM vaccine in infancy compared with those who were not primed or who were primed with two doses of the MenC-CRM vaccine. Conclusion Immunologic memory can be demonstrated by a MenCC booster vaccination but is affected by the type and number of MenCC doses used for infant priming. The MenC rSBA responses can be used to demonstrate successful immunologic priming.